2016
DOI: 10.2215/cjn.04030416
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 Levels and Postangioplasty Restenosis of Arteriovenous Fistulas

Abstract: Circulating monocyte chemoattractant protein-1 levels were elevated 2 days and 2 weeks after percutaneous transluminal angioplasty. Early postangioplasty increase of monocyte chemoattractant protein-1 level was associated with restenosis of arteriovenous fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…104 The association of inflammatory markers and NIH has been demonstrated, but consistent literature in this setting is lacking. [105][106][107][108][109] An interesting recent paper from Hu et al 108 reported a positive correlation between IL-6 and AVF blood flow (Qa). In addition, besides a higher AVF Qa, higher inflammation levels were associated with cardiovascular morbidity.…”
Section: Inflammationmentioning
confidence: 98%
“…104 The association of inflammatory markers and NIH has been demonstrated, but consistent literature in this setting is lacking. [105][106][107][108][109] An interesting recent paper from Hu et al 108 reported a positive correlation between IL-6 and AVF blood flow (Qa). In addition, besides a higher AVF Qa, higher inflammation levels were associated with cardiovascular morbidity.…”
Section: Inflammationmentioning
confidence: 98%
“…The systemic changes of CKD, such as increased oxidative stress, changes in circulating cytokines, retention of toxic metabolites, and altered calcium homeostasis may be responsible for the structural and functional changes in the maturation of AV fistulas [14]. Previous studies have shown a negative impact of oxidative stress, cytokines, and calcium metabolism on neointima formation [15,16]. Nonetheless, the role of uremic toxins on venous intimal hyperplasia was less addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In hemodialysis patients, uraemia and dialysis are associated with increased oxidative stress that causes activation of inflammation, release of free radicals, and depletion of protective antioxidant. Recent studies have shown that pro-inflammatory chemokines and oxidative stress markers are implicated in venous intimal hyperplasia of dialysis vascular access 10,11,34 . Experimental studies also demonstrated that AA reduced oxidant stress levels, improved endothelial function, and decrease expression of vascular adhesion molecules, growth factors, and chemokines that may play an important role in the neointimal formation 3537 .…”
Section: Discussionmentioning
confidence: 99%
“…Uraemia is associated with increased oxidative stress and depletion of protective antioxidants, which are further complicated by dialysis 9 . Recent studies have demonstrated that oxidative stress and inflammatory cytokines are implicated in the stenosis of dialysis access 10,11 . In animal studies, antioxidants have been shown to prevent restenosis after angioplasty 1214 .…”
Section: Introductionmentioning
confidence: 99%